Jean Cocteau's around-the-world performance - Riordan, Kevin (2020)
Jean Cocteau's 1936 trip is likely the most self-consciously modernist and theatrical. In the midst of what his biographer would call his "lesser decade," Cocteau would mount his most ambitious theatrical production to date, on what Chaplin calls the "stage the size of the world."2For his inspiration, Cocteau worked from a childhood memory of seeing Adolphe d'Ennery and Jules Verne'sAround the World in 80 Daysat the Théâtre du Châtelet. His principal adaptation to that popular play—which was still running, some sixty years after opening—was to make it site-specific, all the way around. Cocteau's around-the-world project playfully seems to engage with, confuse, and disregard all three of Mao and Walkowitz's axes: his performance circles the entire world, while missing most of it; for modernism's conventional time frames, it reenacts a too-early play (1874) too late (1936); and it mixes Cocteau's high modernist credentials with the stuff of popular newspapers, brothels, and amusement parks.